Prognostic implications of the lymph node count after neoadjuvant treatment for rectal cancer. Issue 2 (23rd December 2013) - Persiani, R; Biondi, A; Gambacorta, M A; Bertucci Zoccali, M; Vecchio, F M; Tufo, A; Coco, C; Valentini, V; Doglietto, G B; D'Ugo, D
Abstract: Background: The aim of this study was to investigate the effect of neoadjuvant chemoradiotherapy on the lymph node yield of rectal cancer surgery. Methods: Data for patients who underwent neoadjuvant chemoradiotherapy followed by surgery for resectable rectal cancer from June 1992 to June 2009 were reviewed. The primary outcomes measured were the number of lymph nodes retrieved, their status, and patient survival. Results: In total, 345 patients underwent neoadjuvant chemoradiotherapy followed by surgery, and 95 patients had surgery alone. Neoadjuvant chemoradiotherapy decreased both the median (range) number of lymph nodes retrieved (7 (1–33) versus 12·5 (0–44) respectively; P < 0·001) and the number of positive lymph nodes (0 (0–11) versus 0 (0–16); P = 0·001). After neoadjuvant chemoradiotherapy, the number of retrieved lymph nodes was inversely correlated with tumour regression, and with the interval between treatment and surgery. The 5-year overall and disease-free survival rates were 86·5 and 79·1 per cent respectively. After neoadjuvant therapy, lymph node status was found to be an independent predictor of survival, whereas the number of retrieved lymph nodes did not represent a prognostic factor for either overall or disease-free survival. Conclusion: Low lymph node count after neoadjuvant chemoradiotherapy for rectal cancer does not signify an inadequate resection or understaging, but represents an increased sensitivity to the treatment. Abstract : Low count represents treatment response